Transcription Factors in Schizophrenia: A Current View of Genetic Aspects - Roksana Zakharyan (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2016)
Background: Schizophrenia is a polygenic mental disorder with about 80% heritability. Growing evidence indicated that synaptic dysfunctions contribute to SCZ etiopathogenesis. The context and purpose of the study: Transcription factors play an important role in the regulation of gene expression. Whereas expression analysis of transcription factor has been performed, studies of their genetic variants are limited. The current review article summarizes data on transcription factors early growth response 3 (EGR3), c-fos transcription (FOS), immune early response 5 (IER5), c-jun (JUN), Nk2 Homeobox 1 (NKX2-1), and transcription factor 4 (TCF4) encoding genes in schizophrenia. Results and main findings: An important role of the mentioned genes in this pathology has been identified. Conclusions: We concluded that the genetic variants of the transcription factor encodng genes might contribute to the assessment of disease susceptibility and can find potential use for the development of genetically-driven diagnostic approaches in the future.